1995
DOI: 10.1056/nejm199511023331824
|View full text |Cite
|
Sign up to set email alerts
|

Survival after the Age of 80 in the United States, Sweden, France, England, and Japan

Abstract: For people 80 years old or older, life expectancy is greater in the United States than it is in Sweden, France, England, and Japan. This finding suggests that elderly Americans are receiving better health care than the elderly citizens of other developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
119
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 260 publications
(128 citation statements)
references
References 29 publications
5
119
0
4
Order By: Relevance
“…For example, the quality of and access to health care for the elderly is likely to differ between the United States and Latin American and other foreign countries with concomitant differences in survival outcomes (Ross, Pagan and Polsky 2006). In fact, it has been suggested that mortality of the oldest old in the United States is lower than in Europe and Japan at least in part because of greater availability of medical care for the elderly in the United States (Manton & Vaupel 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the quality of and access to health care for the elderly is likely to differ between the United States and Latin American and other foreign countries with concomitant differences in survival outcomes (Ross, Pagan and Polsky 2006). In fact, it has been suggested that mortality of the oldest old in the United States is lower than in Europe and Japan at least in part because of greater availability of medical care for the elderly in the United States (Manton & Vaupel 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The notion of limited life expectancy should not hinder that effort because survival to the age of 80 years and beyond has been reported to have increased in many developed countries. 26 The remaining life expectancy of a white fe-male age 75 years is estimated to be 11.7 years. 27 Recent data have suggested that laparoscopic staging in elderly patients with gynecologic malignancies appears to be well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…The 38), and with the proposition that higher United States expenditures on LTC better meet the needs of the very elderly than the lower LTC expenditures, and less complete LTC service availability, in Japan (39,40).…”
Section: Discussionmentioning
confidence: 99%